Equations balanced on the previous day |
Zn(s) + 2 AgNO3(aq) = Zn(NO3)2(aq) + 2 Ag(s)
Hg(ii)O = Hg + O =>
Hg(ii)O = Hg + O
NaCl(aq) + AgNO3(aq) = AgCl(s) + NaNO3 =>
NaCl(aq) + AgNO3(aq) = AgCl(s) + NaNO3
C5H10O3N2 + O2 = CO2 + H2O + N2 =>
C5H10O3N2 + 6 O2 = 5 CO2 + 5 H2O + N2
PB(NO3)2(aq) + H2SO4(aq) = PBSO4(s) + HNO3(aq) =>
PB(NO3)2(aq) + H2SO4(aq) = PBSO4(s) + 2 HNO3(aq)
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + HNO3(aq) =>
Ba(NO3)2(aq) + H2SO4(aq) = BaSO4(s) + 2 HNO3(aq)
Mg(s) + H3PO4(aq) = Mg3(PO4)2(s) + H2(g) =>
3 Mg(s) + 2 H3PO4(aq) = Mg3(PO4)2(s) + 3 H2(g)
Ca3(PO4)2(s) + H2SO4(aq) = H3PO4(s) + CaSO4(s) =>
Ca3(PO4)2(s) + 3 H2SO4(aq) = 2 H3PO4(s) + 3 CaSO4(s)
H3PO4(aq) + Mg(OH)2(aq) = H2O(l) + Mg3(PO4)2(s) =>
2 H3PO4(aq) + 3 Mg(OH)2(aq) = 6 H2O(l) + Mg3(PO4)2(s)
TlCl + NaOCl + NaOH = Tl2O3 + NaCl + H2O =>
2 TlCl + 2 NaOCl + 2 NaOH = Tl2O3 + 4 NaCl + H2O
Zn(s) + AgNo3(aq) = Ag(s) + Zn(No3)2(aq) =>
Zn(s) + 2 AgNo3(aq) = 2 Ag(s) + Zn(No3)2(aq)
Ca3(PO4)2(s) + H2SO4(aq) = CaSO4(s) + H3PO4(aq) =>
Ca3(PO4)2(s) + 3 H2SO4(aq) = 3 CaSO4(s) + 2 H3PO4(aq)
Mg3N2(s) + H2O(l) = Mg(OH)2(s) + NH3(g) =>
Mg3N2(s) + 6 H2O(l) = 3 Mg(OH)2(s) + 2 NH3(g)
CuO(s) + HNO3(aq) = Cu(NO3)2(aq) + H2O(l) =>
CuO(s) + 2 HNO3(aq) = Cu(NO3)2(aq) + H2O(l)
(NH4)2S(aq) + Co(NO3)2(aq) = CoS(s) + NH4NO3(aq) =>
(NH4)2S(aq) + Co(NO3)2(aq) = CoS(s) + 2 NH4NO3(aq)
K + CuSO4 = K2SO4 + Cu =>
2 K + CuSO4 = K2SO4 + Cu
Fe(OH)3(s) = Fe2O3(s) + H2O(s) =>
2 Fe(OH)3(s) = Fe2O3(s) + 3 H2O(s)
Mg(OH)2(aq) + H3PO4(aq) = H2O(l) + Mg3(PO4)2(aq) =>
3 Mg(OH)2(aq) + 2 H3PO4(aq) = 6 H2O(l) + Mg3(PO4)2(aq)
Cu(NO3)2(aq) + Na3PO4(aq) = CuPO4(s) + Na3(NO3)2(aq) =>
Cu(NO3)2(aq) + Na3PO4(aq) = CuPO4(s) + Na3(NO3)2(aq)
HNO3(aq) + Ni(s) = Ni(NO3)2(aq) + H2(g) =>
2 HNO3(aq) + Ni(s) = Ni(NO3)2(aq) + H2(g)
Pb(NO3)2(aq) + K2S(aq) = PbS(c) + KNO3(aq) =>
Pb(NO3)2(aq) + K2S(aq) = PbS(c) + 2 KNO3(aq)
Fe2(CO3)3(s) = Fe2O3(s) + CO2(g) =>
Fe2(CO3)3(s) = Fe2O3(s) + 3 CO2(g)
CuO(s) + HNO3(aq) = Cu(NO3)2(aq) + H2O(l) =>
CuO(s) + 2 HNO3(aq) = Cu(NO3)2(aq) + H2O(l)
Na2S(aq) + Cd(NO3)2(aq) = NaNO3(aq) + CdS(s) =>
Na2S(aq) + Cd(NO3)2(aq) = 2 NaNO3(aq) + CdS(s)
Pb(NO3)2(aq) + NaI(aq) = PbI2(s) + NaNO3(aq) =>
Pb(NO3)2(aq) + 2 NaI(aq) = PbI2(s) + 2 NaNO3(aq)
PB(NO3)2(aq) + KI(aq) = PBI2(s) + KNO3(aq) =>
PB(NO3)2(aq) + 2 KI(aq) = PBI2(s) + 2 KNO3(aq)
N2O(g) = N2(g) + O2(g) =>
2 N2O(g) = 2 N2(g) + O2(g)
Cu(s) + AgNo3(aq) = Cu(No3)2(aq) + Ag(s) =>
Cu(s) + 2 AgNo3(aq) = Cu(No3)2(aq) + 2 Ag(s)
Zn(NO3)2 + ZnSO4 = Zn + (NO3)(SO4) =>
Zn(NO3)2 + 2 ZnSO4 = 3 Zn + 2(NO3)(SO4)
CaCl2(aq) + Na3PO4(aq) = Ca3(PO4)2(s) + NaCl(aq) =>
3 CaCl2(aq) + 2 Na3PO4(aq) = Ca3(PO4)2(s) + 6 NaCl(aq)
K2S(aq) + Pb(NO3)2(aq) = KNO3(aq) + PbS(aq) =>
K2S(aq) + Pb(NO3)2(aq) = 2 KNO3(aq) + PbS(aq)
Ca(OH)2(aq) + H3PO4(aq) = Ca3(PO4)2 + H2O =>
3 Ca(OH)2(aq) + 2 H3PO4(aq) = Ca3(PO4)2 + 6 H2O
N2H4(g) + N2O4(g) = N2(g) + H2O(g) =>
2 N2H4(g) + N2O4(g) = 3 N2(g) + 4 H2O(g)
Ca3(PO4)2(s) + H2SO4(aq) = H3PO4(aq) + CaSO4(aq) =>
Ca3(PO4)2(s) + 3 H2SO4(aq) = 2 H3PO4(aq) + 3 CaSO4(aq)
H3PO4(aq) + Mg(OH)2(aq) = H2O(l) + Mg3(PO4)2(s) =>
2 H3PO4(aq) + 3 Mg(OH)2(aq) = 6 H2O(l) + Mg3(PO4)2(s)
Mg3N2(s) + H2O(l) = Mg(OH)2(aq) + NH3(g) =>
Mg3N2(s) + 6 H2O(l) = 3 Mg(OH)2(aq) + 2 NH3(g)
Pb(NO3)2(aq) + K2S(aq) = PbS(c) + KNO3(aq) =>
Pb(NO3)2(aq) + K2S(aq) = PbS(c) + 2 KNO3(aq)
SnO2 + H2O = Sn(OH)4 =>
SnO2 + 2 H2O = Sn(OH)4
Ga2O3(s) + H2O(aq) = Ga(OH)3(s) =>
Ga2O3(s) + 3 H2O(aq) = 2 Ga(OH)3(s)
Co(NO3)3(aq) + Zn(s) = Zn(NO3)2(aq) + Co(s) =>
2 Co(NO3)3(aq) + 3 Zn(s) = 3 Zn(NO3)2(aq) + 2 Co(s)
Ca3(PO4)2(s) + H2SO4(aq) = Ca(H2PO4)2(aq) + CaSO4(s) =>
Ca3(PO4)2(s) + 2 H2SO4(aq) = Ca(H2PO4)2(aq) + 2 CaSO4(s)
(CaSO4)2*2H2O + H2O = CaSO4*2H2O =>
(CaSO4)2*2H2O + 2 H2O = 2 CaSO4*2H2O
MgCl2(aq) + Na3PO4(aq) = Mg3(PO4)2(aq) + NaCl(aq) =>
3 MgCl2(aq) + 2 Na3PO4(aq) = Mg3(PO4)2(aq) + 6 NaCl(aq)
Ba(OH)2(aq) + H2SO4(aq) = BaSO4(s) + H2O(l) =>
Ba(OH)2(aq) + H2SO4(aq) = BaSO4(s) + 2 H2O(l)
Ca3(PO4)2(s) + H2SO4(aq) = H3PO4(aq) + CaSO4(aq) =>
Ca3(PO4)2(s) + 3 H2SO4(aq) = 2 H3PO4(aq) + 3 CaSO4(aq)
Hg(ii)O = Hg + O =>
Hg(ii)O = Hg + O
K2S(aq) + Pb(NO3)2(aq) = K2(NO3)2 + PbS =>
K2S(aq) + Pb(NO3)2(aq) = K2(NO3)2 + PbS
K + CuSO4 = KSO4 + Cu =>
K + CuSO4 = KSO4 + Cu
Ba(NO3)2(aq) + H2SO4(aq) = HNO3(aq) + BaSO4(aq) =>
Ba(NO3)2(aq) + H2SO4(aq) = 2 HNO3(aq) + BaSO4(aq)
Cu(NO3)2(aq) + KOH(aq) = Cu(OH)2(s) + KNO3(aq) =>
Cu(NO3)2(aq) + 2 KOH(aq) = Cu(OH)2(s) + 2 KNO3(aq)
Balance the equation of any chemical reaction
Equations balanced on the previous day |
Equations balanced on 01/04/25
Equations balanced on 02/03/24
Please let us know how we can improve this web app.